Efek Antinyeri Ekstrak Etanol Buah Belimbing Wuluh (Averrhoa bilimbi L) pada Mencit yang Diinduksi Asam Asetat - Kemila, Mira; Suprasetya, Edy; Laga, ,Arifson Umbu (Pharmaceutical and Biomedical Sciences Journal (PBSJ), 2023)
Pain is an unpleasant combination of sensory and emotional experience linked to the potential or actual of tissue damage. Typically, pain arises from stimulation of peripheral receptors, which send impulses through pain pathways to the brain. Starfruit is a medicinal plant that is used empirically as an analgesic. This study aims to determine the analgesic effect of starfruit extract on the stretch index and pain protection ratio against acetic acid-induced mice. This study used 25 mice divided into three test groups: one control group (Na-CMC) and one comparison group (Mefenamic acid). The results showed that starfruit can reduce the pain stretch index and have a pain protection ratio compared to the control group. A dose of 250 mg/kg has an analgesic protection ratio of 75.75%, and a dose of 500 mg/kg has a protection ratio of 85.14%. Thus, based on the results of this study, it can be seen that starfruit has the ability to act as an anti-pain.